efisiensi pengolahan limbah domestik menggunakan metode multi soil layering (msl) - Crhisti Riantika, Sonia Megah; Haribowo, Riyanto (Jurnal Mahasiswa Jurusan Teknik Pengairan, 2018)
Domestic waste is a major of polluters especially river. Pollution of domestic waste to river in urban area reaches 60%. Existing pollution causes a decrease in water quality in water bodie. In this research domestic waste processing using Multi Soil Layering (MSL)method. This research purpose to determine the efficiency MSL reactor to manages domestic waste, determine the efficiency of TSS, TDS, and pH, and compare the results of domestic waste treatment with MSL and  available Wastewater Treatment Plant. The result obtained will be compared with Permen LH No.68 Tahun 2016 and PermenKes No. 416 Tahun 1990. From the research get average efficiency for TSS, TDS, and pH is 53.10%;12.85%;5.03% for zeolite, 28.03%;4.47%;6.11% forgravel, 44.35%;10.37%;4.47% forzeolite and gravel, 64.55%;24.52%;4.89% for soil and coconut shell charcoal, 57.53%;21.31%;4.45% forsoil and sawdust, and 63.47%;19.71%;4.24% for soil and rice straw charcoal. From the result calculation efficiency can conclude reactor MSL methodsoil and coconut shell charcoal is the best result to purify the domestic waste of Tlogomas village.